The effect of rural population density on socio economic characteristics of rural communities review of literature / Ayoob Khaleel Ismael and Ibrahim Ngah - Ismael, Ayoob Khaleel; Ngah, Ibrahim (Universiti Teknologi MARA, Perlis, 2011)
Rural population density has a very significant independent influence over important demographic and socioeconomic characteristics of world rural communities. That’s why, this paper try to explain the concept of population density and determine later the factors that affect it. Then it attempt to find out the specific significance of rural population density as an important variable in understanding the demographic and socio-economic characteristic of settled rural regions, where rural density and characteristic presents both practical and conceptual problems for rural planners. In conclusion, the paper demonstrated that rural population density is an important phenomenon in rural communities.